Covid-19 and Pregnancy: An Overview - Castro, Pedro; Matos, Ana Paula; Werner, Heron; Lopes, Flávia Paiva; Tonni, Gabriele; Araujo Júnior, Edward (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Since the World Health Organization (WHO) declared coronavirus infection (COVID-19) a Public Health Emergency of International Concern in January 2020, there have been many concerns about pregnant women and the possible effects of this emergency with catastrophic outcomes in many countries. Information on COVID-19 and pregnancy are scarce and spread throughout a few case series, with no more than 50 cases in total. The present review provides a brief analysis of COVID-19, pregnancy in the COVID-19 era, and the effects of COVID-19 on pregnancy.
Keywords: COVID-19; pregnancy; prenatal care; delivery